Intermetallic phases in Al–Si based cast alloys: new perspective. (2014) - Samuel, E.; Samuel, A. M.; Doty, H. W.; Valtierra, S.; Samuel, F. H.
<x content-type="archive" xml:space="preserve">Abstract</x> The present work was performed on experimental Al–Si near eutectic cast alloys, with different additives mainly Fe, Mg, Mn, Cr, Sr and P. The alloys were cooled at 0·8°C s−1, very close to equilibrium conditions. Precipitated phases, primarily Fe, Cu, Mg and Sr based intermetallics, were examined. Although the phases reported in the present work were documented previously, the range of chemical composition of each phase was confirmed using an electron probe microanalyser equipped with wavelength dispersive spectroscopy and electron dispersive X-ray spectroscopy facilities.